Examining Border Relations and Nation-Building: Nigeria and its Neighbors from 1960 to 2002 - Okorn, Felix Tabi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This study explores the challenge of nation-building in various African nations, especially those characterized by diverse ethnic compositions and religious differences. It highlights how colonial-era borders, established during the partitioning of Africa in 1884 and 1885, have hindered efforts to build unified national identities and foster socio-economic cooperation among ethnic groups. Focusing on Nigeria and its neighboring countries, the research assesses strategies employed to promote nation-building through trans-border relations programs. The colonial legacy left Nigeria and other African nations grappling with complex border issues, exacerbated by post-independence policies that strained cross-border relations and led to diplomatic disputes. Despite these challenges, Nigeria pursued a policy of enhancing relations with neighboring countries, recognizing the interconnectedness of border communities. The establishment of joint commissions, such as the Nigerian Boundary Commission (NBC), aimed to tackle border disputes and promote cooperation. Through trans-border cooperation workshops, the NBC convened stakeholders from diverse backgrounds to discuss and resolve border-related challenges. Despite obstacles such as funding constraints and delays, these workshops remain essential platforms for dialogue, crucial for resolving border issues and promoting nation-building. The study concludes by highlighting the significance of the NBC's initiatives in setting a precedent for other African countries seeking to improve relations with their neighbors through informed dialogue and cooperation.